Professional reflection as a condition of formation of innovational activity of the future teacher (Pedagogy of Higher and Secondary Education, 2007)
In the article is examined and is determined psychological -pedagogical aspect of forming of professional reflection in the conditions of innovative activity offuture teachers.
Keywords: reflection; psychological mechanisms of reflection; pedagogical terms of forming of reflection; alienation; self-identification; professional «І-conception»